Provision of smoking cessation support for pregnant women in England: results from an online survey of NHS stop smoking services for pregnant women - Fahy, Samantha; Cooper, Sue; Coleman, Tim; Naughton, Felix; Bauld, Linda (BioMed Central, 2014)
Background Smoking during pregnancy is a major public health concern and an NHS priority. In 2010, 26% of UK women smoked immediately before or during their pregnancy and 12% smoked continuously. Smoking cessation support is provided through free at the point of use Stop Smoking Services for Pregnant women (SSSP). However, to date, little is known of how these services provide support across England. The aim of this study was to describe the key elements of support provided through English SSSP.